2010
DOI: 10.1111/j.1600-0625.2010.01161.x
|View full text |Cite
|
Sign up to set email alerts
|

Identifying melanogenesis inhibitors from Cinnamomum subavenium with in vitro and in vivo screening systems by targeting the human tyrosinase

Abstract: are equal contributions to this paper.Abstract: Tyrosinase is known to be the first two and rate-limiting enzyme in the synthesis of melanin pigments responsible for colouring skin, hair and eyes. Tyrosinase inhibition is one major strategy used to treat hyperpigmentation. In human skin melanocytes, the cellular tyrosinase inhibition was examined by the conversion of L-tyrosine and oxidation of L-DOPA to dopaquinone. We evaluated the skin pigmentation inhibitor effects with both in vitro and in vivo systems to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
95
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(96 citation statements)
references
References 52 publications
0
95
0
Order By: Relevance
“…1) is a butanolide constituent isolated from the stems of Cinnamomum subavenium. Previous studies have shown that subamolide A exerts its cytotoxic effect on human colorectal cancer cells and inhibitory effect of pigmentation on the skin Wang et al, 2011). However, the effect on human urothelial carcinoma cells has not yet been evaluated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1) is a butanolide constituent isolated from the stems of Cinnamomum subavenium. Previous studies have shown that subamolide A exerts its cytotoxic effect on human colorectal cancer cells and inhibitory effect of pigmentation on the skin Wang et al, 2011). However, the effect on human urothelial carcinoma cells has not yet been evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Cinnamomum subavenium has long been used as a traditional Chinese medicine as recorded in ancient medical literatures for treating a variety of ailments including carcinomatous swelling, stomachache, chest pain, abdominal pain, hernia, diarrhea, rheumatism, nausea and vomiting (Hu, 1998;Xie, 1996). Constituents isolated from Cinnamomum subavenium by column chromatography had been shown with potent cytotoxic and genotoxic effects in several human cancer cell lines Kuo et al, 2008;Shen et al, 2010;Wang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…This is supported by the fact that compound 6d also inhibited TYR activity in A375 cells by 91% in relative to untreated control at a concentration of 50 µg/mL [52]. As compared to compound 6d, the Haginin-A is a non-competitive inhibitor that exhibits relatively strong depigmenting activity in the zebrafish model and decreased its intracellular TYR activity [52,73]. Other compounds such as oleoylethanolamide reduced the body pigmentation in the zebrafish model to about 49.5% (in relative to untreated control) at concentration of 150 µM [78].…”
Section: Application Of Zebrafish Modelmentioning
confidence: 99%
“…Replacing the mammalian model with the zebrafish embryo model for evaluation of efficacy and safety of depigmenting compounds is an interesting topic of discussion in the skin-care industry [73,74,75,92,107,108,109,110,111,112,113,114]. However, in the cosmetic or even dermatological industry, these compounds are formulated in combination of a carrier or vehicle to facilitate its effect on human skin [73,74,79,86,115].…”
Section: Recommendationsmentioning
confidence: 99%
“…However, some authors have reported that the antioxidant activity of phenolics may be related to their redox properties, which enable them to act as reducing agents or hydrogenatom donors, as well as their ability to chelate metals, inhibit lipoxygenase and scavenge free radicals (Martínez-Valverde, Periago, & Ros, 2000). Previous investigations also have demonstrated that scavengers of reactive species such as ascorbic acid derivatives, catalase (CAT) and glutathione (GSH) may significantly inhibit of melanogenesis and down-regulate hyperpigmentation (Panich et al, 2010;Wang, Chen, & Wen, 2010). This study evaluated the antioxidant properties of origanoside from O. vulgare through several chemical and biochemical assays; these are DPPH• radical scavenging activity, ABTS• + radical scavenging activity, O 2 • − scavenging capacity, reducing power, metal chelating activity, capacity to inhibit of lipid peroxidation (LP) using liposome, and capacity to inhibit formation of thiobarbituric acid reactive substances (TBARSs) in mice brain and liver tissue.…”
Section: Introductionmentioning
confidence: 99%